Hubungan Antara Citra Tubuh Dengan Gejala Dismorfik Tubuh Pada Remaja di Masa Pandemi Covid-19 - Theresia, Natalia; Ompusunggu, Henny Erina Saurmauli; Marpaung, Okto (Universitas HKBP Nommensen, 2025)
Background: Body dysmorphics are psychological symptoms where sufferers experience an excessive obsession with minimal and even imaginary physical disabilities. One of the factors that cause the appearance of a sense of dissatisfaction with oneself or what is known as a symptom of body dysmorphics is body image. A person with a positive body image will find themselves attractive, both according to themselves and according to others or at least can accept themselves as they are in contrast to someone with a negative body image, they will consider themselves unattractive. The purpose of this study was to determine the relationship between body image and body dysmorphic symptoms in adolescents during the COVID-19 pandemic. Case: This study was observational analytical study with a cross-sectional design. Sample selection using purposive sampling method with a total sample of 100 high school teenagers in Medan Kota District in 2022. Univariate analysis is displayed in tabular form and bivariate assays are performed using chi-square tests. Discussion: The result of this study, 89% of respondents classified as positive body image and 86% did not have symptoms of body dysmorphic. The relationship of body image with body dysmorphic symptoms was analyzed with the Chi-Square test and found a p value = 0.000.Conclusion: there is a relationship between body image and body dysmorphic symptoms in adolescents during the COVID-19 pandemic. Keywords: Body image, Body dysmorphic symptoms, adolescents